Industry 4.0: Trends in Management of Intelligent Manufacturing Systems - Knapčíková, Lucia; Balog, Michal (EAI/Springer Innovations in Communication and Computing,, 2019)
This book provides a comprehensive exchange of information on current developments in the management of manufacturing systems and Industry 4.0. The book's contributions establish channels of communication and disseminate knowledge among professionals working in manufacturing and related institutions. It features submissions from experts, researchers, academicians and practitioners in relevant fields, who share their knowledge from the field of management of manufacturing systems. The book's main theme is Management of Manufacturing Systems with support for Industry 4.0, Logistics and Intelligent Manufacturing Systems and Applications, Cooperation management and its effective applications. Topics include Logistics, RFID Applications, Industrial and Smart Logistics, Intelligent Manufacturing Systems and Applications, New Materials and Smart Technologies for Industry 4.0, Enterprise Information Systems, Innovation and Knowledge Management, and Sequencing solutions for Lean Manufacturing.